Immunotherapy Duration and Risk of Psychosocial Emotion and Risk of Attention Deficit Hyperactivity Disorder Prevalence and Relation in Allergic Rhinitis Children - Dinda Anes Tunjungsari; Anang Endaryanto; Ahmad Suryawan; Ariyanto Harsono; Zahrah Hikmah; Azwin Mengindra Putera (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Allergic rhinitis (AR) is the most common chronic disease in children. Allergic symptomsaffect daily activities and increase risk of psychosocial emotion and attention deficit hyperactivity disorder(ADHD). Immunotherapy has been proven in improving AR symptomsObjective: To identify prevalence of the risk of psychosocial emotion disorder and ADHD and its relationwith immunotherapy duration in AR children.Methods: A cross-sectional study was held in AR children aged 4-18 years at Allergy Immunology OutpatientClinic, Dr. Soetomo Hospital, during March 2017. Immunotherapy duration categorized into 0-6 months, 6months-1 year, 1-2 years, 2-3 years. Psychosocial emotion disorder risk assessed using Pediatric SymptomsChecklist 17 (PSC-17), scored into four different subscales: Internalizing, Externalizing, Attention, andTotal Score. ADHD risk was assessed using Abbreviated Conner’s Rating Scale (ACRS). Statistical analysisusing One-Way ANOVA and Eta test, with a value of p< 0.05 considered as significant.Results: Total of 37 children included. Based on immunotherapy duration 0-6 months, 6 months-1 year, 1-2years, and 2-3 years, prevalence risk of ADHD are 20.6%, 15.4%, 12.5%, and 12.5%, and prevalence ofpsychosocial emotion disorder risk are only in immunotherapy duration 6 months-1 year 12.5%. There wereno correlation between immunotherapy duration with risk of psychosocial emotion disorder (p = 0.945) andsignificantly correlated to ADHD (p = 0.049, r = 0.326).Conclusion: Prevalence risk of ADHD decrease as the immunotherapy duration increase and immunotherapyduration weakly correlated with risk of ADHD.